Ultrastructural analysis of spores from diverse Bacillales species isolated from Brazilian soil. Issue 2 (3rd December 2018) - de Andrade Cavalcante, Danilo; De‐Souza, Marlene Teixeira; de Orem, Juliana Capela; de Magalhães, Maria Inês André; Martins, Paulo Henrique; Boone, Tyler J.; Castillo, José A.; Driks, Adam
Summary: Many species in the order Bacillales form a specialized cell type called a spore that is resistant to a range of environmental stresses. Transmission electron microscopy (TEM) reveals that the spore is comprised of a series of concentric shells, surrounding an interior compartment harbouring the spore DNA. The outermost of these shells varies considerably in morphology among species, likely reflecting adaptations to the highly diverse niches in which spores are found. To better characterize the variation in spore ultrastructure among diverse species, we used TEM to analyse spores from a collection of 23 aerobic spore‐forming bacteria from the Solo do Distrito Federal (SDF strains), spanning the genera Bacillus, Lysinibacillus, Paenibacillus and Brevibacillus, isolated from soil from central Brazil. We found that the structures of these spores varied widely, as expected. Interestingly, even though these isolates are novel strains of each species, they were structurally very similar to the known examples of each species in the literature. Because in most cases, the species we analysed are poorly characterized, our data provide important evidence regarding which structural features are likely to be constant within a taxon and which are likely to vary.